Investigating the impact of different organics on calcium oxalate crystallization in a synthetic urinary environment - Bottrill, Odin (Curtin University, 2021)
This project looked at 16 additives on the crystallisation of calcium oxalate in a synthetic urinary medium. The additives were assessed for their impact on size, shape and number of crystals formed. It was found that the impact of the different additives was specific to the molecular shape, the number of carboxylic acid groups in the additive and the possibility of hydrogen bonding. Despite this promising candidates were identified for further investigation.